NRF2 signalling pathway: New insights and progress in the field of wound healing. Issue 13 (18th June 2021) - Liu, Yang; Yang, Xiaofan; Liu, Yutian; Jiang, Tao; Ren, Sen; Chen, Jing; Xiong, Hewei; Yuan, Meng; Li, Wenqing; Machens, Hans‐Günther; Chen, Zhenbing
Abstract: As one of the most common pathological processes in the clinic, wound healing has always been an important topic in medical research. Improving the wound healing environment, shortening the healing time and promoting fast and effective wound healing are hot and challenging issues in clinical practice. The nuclear factor‐erythroid–related factor 2 (NFE2L2 or NRF2) signalling pathway reduces oxidative damage and participates in the regulation of anti‐oxidative gene expression in the process of oxidative stress and thus improves the cell protection. Activation of the NRF2 signalling pathway increases the resistance of the cell to chemical carcinogens and inflammation. The signal transduction pathway regulates anti‐inflammatory and antioxidant effects by regulating calcium ions, mitochondrial oxidative stress, autophagy, ferroptosis, pyroptosis and apoptosis. In this article, the role of the NRF2 signalling pathway in wound healing and its research progress in recent years are reviewed. In short, the NRF2 signalling pathway has crucial clinical significance in wound healing and is worthy of further study.